MAKNA FILOSOFI AJARAN SIWA BUDDHA DALAM LONTAR BUBUKSAH - I Made Gami Sandi Untara; I Nyoman Suardika (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2019)
Lontar Bubuksah is an imaginative story script about a religious literary work, as a religiously breathtaking story expressing the ideals and essence of liberating the soul towards pure nature, Moksa, in the Bubuksah text there is a text structure consisting of synopsis, incidents, plots, themes, characterization and mandate. The teachings of Shiva Buddha contained in Lontar Bubuksah are a) The value of Religion in Lontar Bubuksah tends to be Masteristic in nature which takes the source of the Shiva doctrine (Bhatara Guru) as the supreme deity. Gagakaking represents the Shiva doctrine while Bubuksah represents Buddhist doctrine. b) The value of Chastity in Lontar Bubuksah is played by Gagakaking with all its behavior based on spiritual purity (understanding sudha sridanta) c) The Lascarya value in Lontar Bubuksah played by Bubuksah by keeping the patinya and all kinds of behavior that carry out the brata  understand bherawa samyadnyana). The meaning of Shiva Buddha's teachings contained in Lontar Bubuksah are 1) Religious Meanings, 2) Happiness Meanings, 3) Liberation Meanings and 4) Shiva and Buddhist Meanings which can be seen through the two main figures namely Gagakaking is a refresentation of Shivaism and Bubuksah as a refresentation of Buddhism